2016
DOI: 10.1038/srep31670
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring particle translocation via dielectrophoresis in pore channels

Abstract: Understanding and controlling electrophoretic motions of nanoscopic objects in fluidic channels are a central challenge in developing nanopore technology for molecular analyses. Although progress has been made in slowing the translocation velocity to meet the requirement for electrical detections of analytes via picoampere current measurements, there exists no method useful for regulating particle flows in the transverse directions. Here, we report the use of dielectrophoresis to manipulate the single-particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…The variation in the tunnelling current was expected to diminish by controlling the molecular conformations residing in the electrode gap through the DEP mechanism. 149 Barik et al have demonstrated an ultralow-power DEP using nanogap electrodes fabricated via atomic layer lithography to trap the 30 nm PS beads, which can potentially enable high-density integration on a chip and portable biosensing, as shown in Fig. 6B.…”
Section: Trapping Of Single-sized Ps Beadsmentioning
confidence: 99%
“…The variation in the tunnelling current was expected to diminish by controlling the molecular conformations residing in the electrode gap through the DEP mechanism. 149 Barik et al have demonstrated an ultralow-power DEP using nanogap electrodes fabricated via atomic layer lithography to trap the 30 nm PS beads, which can potentially enable high-density integration on a chip and portable biosensing, as shown in Fig. 6B.…”
Section: Trapping Of Single-sized Ps Beadsmentioning
confidence: 99%
“…A slower translocation speed leads to higher resolution and accuracy of the detection and recognition of translocating objects, since the detection is based on the transient changes in ionic or tunneling current [60] during translocation. In contrast, we prefer a high translocation frequency f detect to carry out stochastic analysis of the detected signals [70]. Therefore, increasing f detect while slowingū x is desired for better detection performance of objects translocating the contraction geometry, such as in nanopore sensors.…”
Section: Tuning Translocation Velocity and Frequencymentioning
confidence: 99%
“…In the detection process, the velocities of targets through the nanopore are important because the velocity-control performance is directly related to the sensor accuracy. Various velocity-control techniques have been applied inside the nanopore [60][61][62]: tethering a protein larger than the nanopore diameter to prevent fast translocation [63,64], coating nanopore walls with counteractive charges [65,66] or polymers [67], using active feedback control with an applied voltage [68], decreasing the temperature to increase the viscosity of the solvent [69], and inplane guiding of targets via dielectrophoresis by AC electric fields at the nanopore entrance [70]. However, most of these techniques need highly sophisticated fabrication apparatuses and experimental skills.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of manipulation techniques of such nanoscale targets in nanochannels is expected to improve the performance of the nanofluidic devices, providing a higher detection frequency and/or a finer signal resolution. In recent years, some efforts have been made to control the translocation of particles (Yusko et al 2011;Keyser 2011;Tanaka et al 2016). However, complicated fabrication processes of nanofluidic devices are necessary for these approaches, and the development of feasible methods is expected to expand the usefulness of nanofluidic devices to various research fields.…”
Section: Introductionmentioning
confidence: 99%